Adsorption of Methylene Blue using Composite Fe3o4-Activated Charcoal Cassava Skin (Manihot esculenta C.) - Duwi Devi Wulandari; Soerja Koesnarpadi; Noor Hindryawati (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Preparation of Fe3O4 activated cassava shell charcoal composite (Fe3O4-AAKS) by coprecipitation method, namely mixing activated cassava shell charcoal (AAKS) with FeCl3.6H2O and FeSO4.7H2O solutions using a mole ratio of 3:2 in alkaline conditions with the addition of 25% NH4OH has been carried out. The Fe3O4-AAKS composite was characterized using Fourier Transform Infra-Red (FTIR) and X-Ray Diffraction (XRD) instruments, then the composite material was applied to adsorb methylene blue with variations in the influence of contact time, optimum concentration and optimum adsorbent mass and determined the adsorption isotherm model. The results of the characterization of Fe3O4-AAKS with FTIR showed that a composite had been formed which was marked by the appearance of absorption at wave number 1033,85 cm-1 indicating the presence of a C-O group and the appearance of a typical absorption of Fe-O groups at 540,07 cm-1. Fe3O4-AAKS XRD results show an amorphous charcoal diffraction pattern at an angle of 20º-30º and a magnetic phase iron oxide diffraction pattern of Fe3O4 at 2 θ at angles of 18.59º, 30.38º, 35.62º, 43.56º, 53.85º, 57.30º, 62.90º and 74.62º. Methylene blue adsorption application using Fe3O4-AAKS composite showed optimum conditions at contact time of 30 minutes, optimum concentration at 60 mg/L with optimum adsorbent mass of 0.05 gram. The adsorption pattern of the composite material follows the Langmuir isotherm with a maximum adsorption capacity of 25.38 mg/g.